Salmeterol, a β2 Adrenergic Agonist, Promotes Adult Hippocampal Neurogenesis in a Region-Specific Manner - Bortolotto, Valeria; Bondi, Heather; Cuccurazzu, Bruna; Rinaldi, Maurizio; Canonico, Pier Luigi; Grilli, Mariagrazia (Frontiers in Pharmacology, 2019)
Neurogenesis persists in the subgranular zone of the hippocampal formation in the adult mammalian brain. In this area, neural progenitor cells (NPCs) receive both permissive and instructive signals, including neurotransmitters, that allow them to generate adult-born neurons which can be functionally integrated in the preexisting circuit. Deregulation of adult hippocampal neurogenesis (ahNG) occurs in several neuropsychiatric and neurodegenerative diseases, including major depression, and represents a potential therapeutic target. Of interest, several studies suggested that, both in rodents and in humans, ahNG is increased by chronic administration of classical monoaminergic antidepressant drugs, suggesting that modulation of this process may participate to their therapeutic effects. Since the established observation that noradrenergic innervations from locus coeruleus make contact with NPC in the dentate gyrus, we investigated the role of beta adrenergic receptor (β-AR) on ahNG both in vitro and in vivo. Here we report that, in vitro, activation of β2-AR by norepinephrine and β2-AR agonists promotes the formation of NPC-derived mature neurons, without affecting NPC survival or differentiation toward glial lineages. Additionally, we show that a selective β2-AR agonist able to cross the blood–brain barrier, salmeterol, positively modulates hippocampal neuroplasticity when chronically administered in adult naïve mice. Indeed, salmeterol significantly increased number, maturation, and dendritic complexity of DCX+ neuroblasts. The increased number of DCX+ cells was not accompanied by a parallel increase in the percentage of BrdU+/DCX+ cells suggesting a potential prosurvival effect of the drug on neuroblasts. More importantly, compared to vehicle, salmeterol promoted ahNG, as demonstrated by an increase in the actual number of BrdU+/NeuN+ cells and in the percentage of BrdU+/NeuN+ cells over the total number of newly generated cells. Interestingly, salmeterol proneurogenic effects were restricted to the ventral hippocampus, an area related to emotional behavior and mood regulation. Since salmeterol is commonly used for asthma therapy in the clinical setting, its novel pharmacological property deserves to be further exploited with a particular focus on drug potential to counteract stress-induced deregulation of ahNG and depressive-like behavior.